Validation of new diagnostic indices to simplify hyponatremia therapy assessment in patients on thiazide diuretics: study protocol of a randomized, controlled, parallel-group trial (THAT-Study) - Karin Vogt; David Widmer; Mark Kirsch; Mirjam Christ-Crain; Laura Potasso (Trials)
Abstract Background Thiazide or thiazide-like diuretics associated hyponatremia (TAH) has a high prevalence in hospitalized patients. Patients might present either with hypovolemic hyponatremia due to volume loss as a diuretic effect of thiazide or with a thiazide-induced syndrome of inadequate antidiuresis-like hyponatremia in need of fluid restriction. Sodium-based urine indices are usually not able to differentiate these two, being directly influenced by thiazide itself. Current guidelines suggest the use of clinical hydration status assessment in patients with TAH, but this approach has a poor diagnostic performance. In a retrospective analysis, we found apparent strong ion difference (aSID) as well as chloride and potassium levels in urine (ChU) to be helpful in the differential diagnosis of TAH. Methods This is a randomized (1:1 ratio) controlled, superiority, parallel-group single-center trial. In total, 136 participants with TAH < 130 mmol/l will be enrolled and randomly assigned to undergo either aSID/ChU-guided therapy of TAH or standard of care during hospitalization. At baseline, hydration status will be assessed by history/clinical examination and ultrasound. The primary outcome is the percentage of patients with an increase in serum sodium level > 4 mmol/l at day 1 or > 134 mmol/l in a maximum of 3 days in the aSID/ChU guided therapy group as compared to the standard care group. Discussion This study will prospectively investigate whether the implementation of 2 new diagnostic indices (aSID and, if inconclusive, ChU) allows for a correct treatment of TAH. As a secondary outcome, the performance of clinical and ultrasound-guided hydration status assessment will be investigated. Trial registration ClinicalTrials.gov, identifier: NCT06381934 . Registered on 19 April 2024. www.kofam.ch , identifier: SNCTP 000005848/BASEC2024-00335.